Growth Kinetics Determination Using Different Mathematical Models for Microalgae Characium sp. UKM1, Chlorella sp. UKM2 and Coelastrella sp. UKM4 - Mohamad Faisal Ni Aznan; NAZLINA HAIZA MOHD YASIN; Norzila Mohd; Mohd Sobri Takriff (ASM Science Journal, 2022)
Microalgae are extensively used in industry due to their potential in producing high-value metabolites. The good microalgae growth kinetics performance is essential owing to excellent microalgae biomass harvesting efficiency. Therefore, the best mathematical model for the growth kinetics of microalgae is required to predict the correct growth kinetics value and helps in the elucidation of downstream processes. This study embarks on the objective to determine the best mathematical models for three local microalgae which are Characium sp. UKM1, Chlorella sp. UKM2 and Coelastrella sp. UKM4 cultured in Bold Basal Media (BBM). The four mathematical models are used to evaluate the growth kinetics of microalgae which include logistic model (Lm), modified logistic model (MLm), modified Gompertz model (MGm) and Baranyi-Roberts model (BRm). The experimental data were compared to the predicted data through the residual plot. The comparison shows that BRm is the best model to fit UKM1, UKM2 and UKM4 due to the experimental data which is close to the x-axis of the residual plot indicating the data were fitted the best to the BRm. The statistical analysis confirmed that all microalgae growth patterns exhibited that the BRm is the best model owing to the lowest percentage of standard error prediction indicating the lowest error compared to the other models. In addition, accuracy and bias factors are near to one which assess the precision of these models. In conclusion, the growth of UKM1, UKM2 and UKM4 grown in BBM is best fitted to the Baranyi-Roberts model.